The Syntheses, Crystal Structure and Luminescence Properties of Cone-Like Octadentate Europium (III) Complexes with Four Short Alkoxy Substituents - Tetsuji Moriguchi; Satoshi Hirosaki; Venkataprasad Jalli; Akihiko Tsuge; Kenji Yoza (Crystals, 2017)
Treatment of 1-(4′-methoxy or ethoxy phenyl)-4,4,4-trifluoro-1,3-butanedione with europium (III) chloride in the presence of piperidine resulted in the halide ligands exchange yielded new piperidinium tetrakis{1-(4′-methoxy or ethoxy phenyl)-4,4,4-trifluoro-1,3-butanedionato} europate (III) complexes 2a and 2b. Complexes 2a and 2b have been characterized by elemental analysis, 1H NMR spectroscopy, and FAB-MS, and their absolute structures were determined by single crystal X-ray diffraction analysis. The complexes 2a and 2b have the monoclinic space groups C2/c (No. 15, 4′-substituent = OCH3) and with P − 1 (No. 2, 4′-substituent = OC2H5), respectively. X-ray analysis results showed that eight coordinate structures of the complexes 2a and 2b have conelike structures, like calix[4]arenes, but their structures were slightly different due to the crystal packing and the existence of the solvent molecule. The complexes 2a and 2b exhibited identical, strong photoluminescence emissions in the solution phase.